NGO Trend Asia's Efforts in Controlling Transboundary Air Pollution in Jakarta: A Case Study of the Suralaya Steam Power Plant - Putri, Salsabil Teratai; Angela, Deni (Journal La Sociale, 2024)
The problem of poor air pollution quality is becoming more serious often in big cities, especially in the capital city of DKI Jakarta. Apart from vehicle emissions, there are other problems that are also important due to the use of Steam Power Plants (PLTU) around the Jakarta area. PLTU Suralaya in Banten is one of the largest sectors that emits the amount of emissions that have an impact on the surrounding area. This study aims to provide a description of the strategy carried out by the Non-Government Organization (NGO) Trend Asia as an effort to control air pollution pollution in Jakarta through transboundary emissions by the Suralaya PLTU. This research uses qualitative case study research methods and will be strengthened by the theory of environmental NGO strategy by MC. Cormick as an analysis knife of this study. The results of this study explain the strategies used by Trend Asia in efforts to control transboundary emission pollution of the Suralaya coal-fired power plant from nine MC strategies. The relevant Cormick used six strategies, namely Working with Elected Officials, Undertaking Research, Campaigning and Organizing Public Protests, Promoting Media Coverage of Environmental Issues, Information Exchange, and Generating Local Community Involvement in Environmental Protection.